Informal Helping Relationship in Work Organizations - Burke, Ronald J.; Weir, Tamara; Duncan, Gordon (Academy of Management Journal, 1976)
Fifty-three managers described informal helping interactions in their work settings from both helper and helpee perspectives. Types of problems, who initiated the interaction, nature of the helping act, and characteristics of the helpers were all examined. Considerable satisfaction and progress was believed to result from these interactions.